A critical examination of K-2 professional learning policy: a discourse analysis of social justice language - Hoffhines, Courtney J. (Kansas State University, 2022)
Today’s teachers must navigate a complex system of policy and curriculum, while striving to accommodate increasingly diverse student demographics and complicated social landscapes. In recognition of the modern-day K-2 classroom, this research reviewed and analyzed educational policy language to identify and examine social justice concepts related to practitioners’ professional roles. Evaluating policy content through careful policy analysis supports a review of professional expectations and learning in relation to the meaning of language and discourse within educational text. Critical discourse analysis methods were used to examine educational policy available through the Kansas State Department of Education. The researcher analyzed the language used to address concepts of social justice education, explored the presence and application of critical pedagogical concepts, as well as identified opportunities for professional expectations in relation to social justice education and professional learning. Study findings, in alignment with core research concepts, were based in language connected to social justice education, use of critical pedagogy, as well as insights into professional learning through professional expectation. Findings include the communication of culturally responsive instructional practices, coded language indicating support for all learners, as well as the appearance of values through social justice education language and concepts. Findings also connected critical pedagogical concepts within demonstrations of Kansas values, tied to professional knowledge and practice. Finally, findings based in professional learning opportunities showed inferred social justice education practices and the integration of civic behaviors. Implications for practice are also discussed through the examination of overarching themes: policy, social justice education, and professional learning, demonstrating educational insights for practitioners and policymakers, as well as support for future research.
Keywords: Social justice education; K-12 schools; Policy analysis; Discourse analysis; Critical pedagogy; Professional learning